Optimized Ribociclib nanostructured lipid carrier for the amelioration of skin cancer: Inferences from ex-vivo skin permeation and dermatokinetic studies - Mohammed F. Aldawsari; Mohammad Azhar Kamal; Mohamed F. Balaha; Talha Jawaid; Mohammed Jafar; Sana Hashmi; Majid Ahmad Ganaie; Aftab Alam (Elsevier, 2024)
Current research focuses on explicitly developing and evaluating nanostructured lipidic carriers (NLCs) for the chemotherapeutic drug Ribociclib (RCB) via the topical route to surmount the inherent bioavailability shortcomings. The absolute oral bioavailability has not been determined, but using a physiologically based pharmacokinetic model it was predicted that 65.8 % of the standard dose of RCB (600 mg) would be absorbed mainly in the small intestine. RCB-NLCs were produced using the solvent evaporation method, and Box-Behnken Design (BBD) was employed to optimize composition. The prepared NLCs had an average PS of 79.29 ± 3.53 nm, PDI of 0.242 ± 0.021, and a %EE of 86.07 ± 3.14. The TEM analysis disclosed the spherical form and non-aggregative nature of the NLCs. The outcomes of an in-vitro release investigation presented cumulative drug release of 84.97 ± 3.37 % in 24 h, significantly higher than that from the RCB suspension (RCB-SUS). Ex-vivo skin permeation investigations on rodent (Swiss albino mice) revealed that RCB-NLCs have 1.91 times increases in skin permeability comparable to RCB-SUS. Compared to RCB-SUS, RCB-NLCs were able to penetrate deeper into the epidermis membrane than RCB-SUS as per the findings of confocal microscopy. In dermatokinetic study, higher amount of RCB was maintained in both the layers of mice's skin when treated with RCB-NLCs gel comparable to the RCB-SUS gel preparation. The in-vitro, ex-vivo, CLSM, and dermatokinetics data demonstrated a significant possibility for this novel RCB formulation to be effective against skin cancer.